2015
DOI: 10.1523/jneurosci.1022-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of Methamphetamine Craving Is Associated with Selective Increases in Expression ofBdnfandTrkb, Glutamate Receptors, and Epigenetic Enzymes in Cue-Activated Fos-Expressing Dorsal Striatal Neurons

Abstract: Cue-induced methamphetamine seeking progressively increases after withdrawal (incubation of methamphetamine craving), but the underlying mechanisms are largely unknown. We determined whether this incubation is associated with alterations in candidate genes in dorsal striatum (DS), a brain area implicated in cue-and context-induced drug relapse. We first measured mRNA expression of 24 candidate genes in whole DS extracts after short (2 d) or prolonged (1 month) withdrawal in rats following extended-access metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(155 citation statements)
references
References 69 publications
12
132
7
Order By: Relevance
“…There was a strong positive correlation between BAZ1B and SMARCA5 binding (r Ï­ 0.873), suggesting that BAZ1B is at least partly working with SMARCA5 to exert its regulation. Agreeing with the previously reported transcriptionally activating role of BAZ1B in other systems (Vintermist et al, 2011;Culver-Cochran and Chadwick, 2013;Lundqvist et al, 2013;Sarshad et al, 2013;Takada, 2015), we found positive correlations between BAZ1B binding and three activating histone marks, H3K4me3 (r Ï­ 0.117), H3K4me1 (r Ï­ 0.279), and H3K27Ac (r Ï­ 0.332), and a negative correlation between BAZ1B and two repressive marks, H3K9me2 (r Ï­ ÏȘ0.165) and H3K9me3 (r Ï­ ÏȘ0.101). Surprisingly, BAZ1B had a significant positive correlation with the repressive mark H3K27me3 (r Ï­ 0.168).…”
Section: Genome-wide Mapping Of Baz1b Binding In Nac Under Cocaine Ansupporting
confidence: 88%
See 1 more Smart Citation
“…There was a strong positive correlation between BAZ1B and SMARCA5 binding (r Ï­ 0.873), suggesting that BAZ1B is at least partly working with SMARCA5 to exert its regulation. Agreeing with the previously reported transcriptionally activating role of BAZ1B in other systems (Vintermist et al, 2011;Culver-Cochran and Chadwick, 2013;Lundqvist et al, 2013;Sarshad et al, 2013;Takada, 2015), we found positive correlations between BAZ1B binding and three activating histone marks, H3K4me3 (r Ï­ 0.117), H3K4me1 (r Ï­ 0.279), and H3K27Ac (r Ï­ 0.332), and a negative correlation between BAZ1B and two repressive marks, H3K9me2 (r Ï­ ÏȘ0.165) and H3K9me3 (r Ï­ ÏȘ0.101). Surprisingly, BAZ1B had a significant positive correlation with the repressive mark H3K27me3 (r Ï­ 0.168).…”
Section: Genome-wide Mapping Of Baz1b Binding In Nac Under Cocaine Ansupporting
confidence: 88%
“…The related ISWI subunit, BAZ1B (also known as WSTF, or Williams Syndrome Transcription Factor), was first discovered by mapping the deletion region of patients with the developmen-tal disorder Williams-Beuren syndrome (Lu et al, 1998;Peoples et al, 1998). The BAZ family of proteins contain a BAZ type of bromodomain (Jones et al, 2000) and BAZ1B in particular is implicated in several chromatin remodeling/transcriptional complexes (including associating with the ISWI subunit, SMARCA5) with diverse roles in regulating DNA replication, DNA repair, and transcription (Bozhenok et al, 2002;Poot et al, 2004;CavellĂĄn et al, 2006;Percipalle et al, 2006;Xiao et al, 2009;Vintermist et al, 2011;Culver-Cochran and Chadwick, 2013;Lundqvist et al, 2013;Sarshad et al, 2013;Takada, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We implanted bilateral guide cannulae (23 gauge; Plastics One) 1 mm above the DMS. The Paxinos and Watson (2008) coordinates (nose bar set at ÏȘ3.3 mm) for DMS were as follows: distance from bregma: anteroposterior, Ï©1.2 mm; mediolateral, Ïź2.4 mm (8°angle); and dorsoventral, ÏȘ4.3 mm Li et al, 2015c). We anchored the cannulas to the skull with jeweler's screws and dental cement.…”
Section: Intracranial Surgerymentioning
confidence: 99%
“…We performed RNA ISH for Fos, Drd1, and Drd2 mRNAs as described previously (Li et al, 2015c;Rubio et al, 2015;. Sixty minutes after the beginning of the test session, we briefly anesthetized the rats with isoflurane (Ïœ30 s) and decapitated them.…”
Section: Rnascope In Situ Hybridization Assaymentioning
confidence: 99%
See 1 more Smart Citation